Updating Winter: The Importance Of Climate-Sensitive Urban Design For Winter Settlements - Chapman, David; Nilsson, Kristina L.; Rizzo, Agatino; Larsson, Agneta (Luleå tekniska universitet, Arkitektur och vatten, 2018)
This study explores winter settlement urban design principles to begin to identify climate related conditions that are affecting soft mobility (walking and cycling) in these communities. Winter communities have evolved lifestyles and means that fit with working and living with local conditions and seasonal variations. With climate change, however, comes evolving weather’s that these communities need to adapt too. These changes may present new risks and unexpected challenges to outdoor soft mobility in the community. Public policy highlights physical inactivity as a major health concern. For these communities, winter has always limited outdoor soft-mobility. Here, we understand that in winter outdoor activity can be reduced by weather and fear of accidents. People’s understanding of the barriers and enablers to soft mobility are also often based on experience and ability to detect environmental clues. To help winter communities maximise the opportunities for outdoor soft mobility and the wellbeing benefits this can bring, built environments need to be designed with an understanding of climate change. This study explores barriers and enablers to soft mobility in winter and discusses them in light of climate change and human wellbeing. It is argued that established principles of urban design may require re-evaluation if we want to increase outdoor soft mobility in winter. Increases in physical activity could help reduce costs and pressures on health services by creating safer and more walkable communities. The paper concludes by suggesting that communities should focus on more context based winter urban design principles that account for ongoing climate change. Validerad;2018;Nivå 1;2018-11-08 (svasva)